AmelOBP4: an antenna-specific odor-binding protein gene required for olfactory behavior in the honey bee (Apis mellifera) - Fang Liu; Yu Lai; Lixian Wu; Qiang Li; Linyue Lei; Wei Yin; Yuan Zhang; Zachary Y. Huang; Hongxia Zhao (Frontiers in Zoology)
Abstract Background Odorant binding proteins (OBPs) initiate the process of odorant perception. Numerous investigations have demonstrated that OBPs bind a broad variety of chemicals and are more likely to carry pheromones or odor molecules with high binding affinities. However, few studies have investigated its effects on insect behavior. Previously, we found that AmelOBP4 has a significantly higher expression in the heads of foragers than that of nurses regardless of their ages, revealing its importance in foraging behaviour of the honey bee. RNA interference (RNAi) is the induction of sequence specific gene silencing by double-stranded RNA (dsRNA), it is a powerful tool that makes gene inactivation possible in organisms that were not amenable to genetic analysis before. Results In this study, we found that AmelOBP4 had high expression levels in the antennae of both nurses and foragers, and could be successfully inhibited by feeding double stranded RNA of AmelOBP4 (dsAmelOBP4). Foragers with inhibited AmelOBP4 showed significantly lower sugar responsiveness than control bees, and also significantly reduced EAG response to plant volatiles of nonanal, linalool and 1-Octen-3ol. On the other hand, nurses with inhibited AmelOBP4 showed significantly reduced EAG response to brood pheromone of ethyl oleate, methyl linoleate, methyl palmitate and β-ocimene. Finally, the Y-tube choice assay showed nurses only exhibited a significantly reduced preference to ethyl oleate, but foragers exhibited significantly reduced preference to all these three plant volatiles. Conclusions The findings of our study suggested that AmelOBP4 plays an important role in the odorant binding process, especially in modulating olfactory behaviour in workers. Our results provide a foundation for exploring the olfactory mechanism of Apis mellifera.